Southeast Asia at the heart of the implementation of the One Health approach - Claire Lajaunie; Serge Morand; Soawapak Hinjoy (Discover Public Health)
Abstract The COVID-19 pandemic spotlighted the One Health approach, notably with the international One Health High-Level Experts Panel jointly created by the Food and Agriculture Organization of the United Nations, the United Nations Environment Programme, the World Organization for Animal Health, and the World Health Organization. These organizations decided to foster the adoption of the One Health approach and put it into action aiming at enhancing countries preparation capacity and capability as well as their ability to prevent, detect, predict, and respond to public health threats, while considering interactions between humans, wildlife and domestic animals and ecosystems. Official declarations, regional and emblematic national policies or mechanisms and regional strategies and plans are put into perspective with the main international events, initiatives and major steps leading to the inception of the One Health approach. Thanks to a retrospective view of the history of the One Health approach, we examine the crucial role of Southeast Asia in its international recognition. We highlight how the region, a hotspot of the emergence of infectious diseases, established policies containing the precursor ingredients of One Health. It is accompanied by the definition of implementation tools and mechanisms which evolved with the Covid-19 pandemic. The One Health approach transforms the framework of international, regional and national governance linking health and the environment and the Southeast Asian countries are at the core of the action.